Harnessing inter-kingdom metabolic disparities at the human-fungal interface for novel therapeutic approaches - Costantini, Claudio; Pariano, Marilena; Puccetti, Matteo; Giovagnoli, Stefano; Pampalone, Gioena; Dindo, Mirco; Cellini, Barbara; Romani, Luigina (Frontiers in Molecular Biosciences, 2024)
Humans interact with a multitude of microorganisms in various ecological relationships, ranging from commensalism to pathogenicity. The same applies to fungi, long recognized for their pathogenic roles in infection - such as in invasive fungal diseases caused, among others, by Aspergillus fumigatus and Candida spp. - and, more recently, for their beneficial activities as an integral part of the microbiota. Indeed, alterations in the fungal component of the microbiota, or mycobiota, have been associated with inflammatory, infectious and metabolic diseases, and cancer. Whether acting as opportunistic pathogens or symbiotic commensals, fungi possess a complex enzymatic repertoire that intertwines with that of the host. In this metabolic cross-talk, fungal enzymes may be unique, thus providing novel metabolic opportunities to the host, or, conversely, produce toxic metabolites. Indeed, administration of fungal probiotics and fungi-derived products may be beneficial in inflammatory and infectious diseases, but fungi may also produce a plethora of toxic secondary metabolites, collectively known as mycotoxins. Fungal enzymes may also be homologues to human enzymes, but nevertheless embedded in fungal-specific metabolic networks, determined by all the interconnected enzymes and molecules, quantitatively and qualitatively specific to the network, such that the activity and metabolic effects of each enzyme remain unique to fungi. In this Opinion, we explore the concept that targeting this fungal metabolic unicity, either in opportunistic pathogens or commensals, may be exploited to develop novel therapeutic strategies. In doing so, we present our recent experience in different pathological settings that ultimately converge on relevant trans-kingdom metabolic differences.